2006
DOI: 10.1111/j.1462-2920.2006.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Exocellular electron transfer in anaerobic microbial communities

Abstract: SummaryExocellular electron transfer plays an important role in anaerobic microbial communities that degrade organic matter. Interspecies hydrogen transfer between microorganisms is the driving force for complete biodegradation in methanogenic environments. Many organic compounds are degraded by obligatory syntrophic consortia of proton-reducing acetogenic bacteria and hydrogen-consuming methanogenic archaea. Anaerobic microorganisms that use insoluble electron acceptors for growth, such as iron-and manganese-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
216
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 365 publications
(228 citation statements)
references
References 112 publications
4
216
0
8
Order By: Relevance
“…For example, as nonfermentative bacteria, Dehalococcoides spp. depend in the environment on the H 2 supplied by other microorganisms (38). Conversely, our results also showed that river water and sediment microorganisms could support the growth and dechlorination activity of Dehalococcoides spp.…”
Section: Discussionsupporting
confidence: 49%
“…For example, as nonfermentative bacteria, Dehalococcoides spp. depend in the environment on the H 2 supplied by other microorganisms (38). Conversely, our results also showed that river water and sediment microorganisms could support the growth and dechlorination activity of Dehalococcoides spp.…”
Section: Discussionsupporting
confidence: 49%
“…The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45]. Recent study demonstrated the possibility of direct interspecies electron transfer (DIET) between Geobacter species and Methanosaeta concilii within upflow anaerobic sludge blanket reactor methanogenic aggregates, which were electrically conductive largely contributed by Geobacter species [32].…”
Section: Discussionmentioning
confidence: 99%
“…The quinone structure allows humics to mediate extracellular electron transfer from a bacterium to an insoluble electron acceptor or to another bacterium [7,45], which was generally demonstrated by the use of AQDS. Under standard condition, AQDS is considered to be incapable of functioning as an electron carrier in methanogenic consortia because the redox potential of AQDS/AH 2 QDS (E 0 ′=−184 mV) is too high to drive CO 2 reduction to methane (E 0 ′ of CO 2 /CH 4 =−240 mV).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that electrons are transferred from ANME to SRB via extracellular redox shuttles (Widdel and Rabus 2001;Wegener et al 2008), via membrane bound redox shuttles or so called ''nanowires'' (Reguera et al 2005;Stams et al 2006;Thauer and Shima 2008;Wegener et al 2008). If this is indeed the case, the methane oxidizers could selectively be grown on a methane-fed anode and the involved sulfate reducers on a sulfate-fed cathode of a microbial fuel cell.…”
Section: Other Incubation Techniquesmentioning
confidence: 99%